Bioimpedance for Oedema Evaluation after Total Knee Arthroplasty. (27th November 2012) - Pichonnaz, Claude; Bassin, Jean‐Philippe; Currat, Damien; Martin, Estelle; Jolles, Brigitte M.
Abstract: Background and Purpose: Electrical bioimpedance spectroscopy (BIS) allows the evaluation of limb extracellular fluid (R0) and total fluid (Rinf). BIS could facilitate post‐surgical oedema evaluation after total knee arthroplasty (TKA), as it is easily performed and is non‐invasive. However, neither its applicability in this context nor the influence of metallic implants on measurement has been evaluated. The aim of this study was to evaluate the influence of TKA implants on the BIS R0 and Rinf variables used for oedema evaluation. Method: This was a prospective non‐randomized comparative clinical trial. One oedema‐free group of patients with TKA was compared with a group presenting similar characteristics except for the arthroplasty, to assess the influence of the implant on BIS measurement in the absence of oedema. The TKA group included 15 patients who had undergone surgery more than a year previously, and the control group included 19 patients awaiting TKA surgery. Volume and perimeter measurements served as reference criterions. The lower limb percentage differences for BIS, knee perimeter and volume were calculated. The significance of differences between groups was calculated for all measurement methods, using the Mann–Whitney test. The setting was a Department of Orthopedic Surgery and Traumatology in a university hospital. Results: The differences between groups were not significant for R0, Rinf, volume and perimeter. R0 showed the smallest mean difference in limb percentage difference between groups [means (SD): TKA 3.98 (8.09), controls 3.97 (5.16)]. Conclusions: The lower‐leg percentage difference in the TKA group is comparable with that of healthy subjects. R0 can be used for oedema evaluation following TKA surgery, as there was no sign of alteration from the metallic implant. These findings indicate the potential for early oedema evaluation after TKA. More research is warranted to extensively validate the application of BIS for oedema evaluation after TKA. Copyright © 2012 John Wiley & Sons, Ltd.